Analysis of HBV X gene quasispecies characteristics by next‐generation sequencing and cloning‐based sequencing and its association with hepatocellular carcinoma progression. Issue 6 (13th February 2019) - Mei, Fanbiao; Ren, Jingjing; Long, Long; Li, Jilin; Li, Kezhi; Liu, Haizhou; Tang, Yanping; Fang, Xiang; Wu, Hanghang; Xiao, Chanchan; Huang, Tianren; Deng, Wei
Abstract: Objectives: This study aimed to describe the differences between next‐generation sequencing (NGS) and cloning‐based sequencing (CBS) in HBX quasispecies research and primitively investigate the relationship between the dominant HBX quasispecies and hepatocellular carcinoma (HCC). Methods: A total of 12 serum samples were collected. Serum hepatitis B virus (HBV) DNA was extracted, and the HBV X‐region (HBX) was amplified by nested polymerase chain reaction (PCR). The PCR products were simultaneously tested with NGS and CBS to detect quasispecies of the HBX. Results: A total of 9348 eligible quasispecies sequences were obtained by NGS, which were much larger than the 98 of that by CBS. By the phylogenetic tree, the dominant quasispecies sequence of each sample could be found, although they had several nucleotides differences between the dominant quasispecies sequences found by CBS and NGS. By comparing the quasispecies heterogeneity, it was found that the quasispecies complexity value of HBV X‐region obtained by NGS was higher than CBS ( P  < 0.05). The diversity values, including d, d S, d N, an d d N/ d S obtained by NGS were lower than by CBS (all of P  < 0.01). The relativity of Spearman(rs) in d, d S, and d N were statistically significant (rs_ d  = 0.865, P  = 0.001; rs_ d S = 0.722, P  = 0.014; and rs_ d N = 0.738, P  = 0.011, respectively). There were 21 different bases between the HBX quasispecies of case A and control B. Conclusion: The results of this can be used as guidance when researchers plan to choose a suitable method to study quasispecies, especially the HBV X gene quasispecies. Some high‐risk mutations of HBX quasispecies were also found in this study and their relationship with HCC need deeper exploration.